Evidence for the effect of depth on visual working memory - Jiehui Qian (Nature Portfolio, 2017)
Abstract Visual working memory (VWM) is a cognitive memory buffer for temporarily holding, processing, and manipulating visual information. Previous studies have demonstrated mixed results of the effect of depth perception on VWM, with some showing a beneficial effect while others not. In this study, we employed an adapted change detection paradigm to investigate the effects of two depth cues, binocular disparity and relative size. The memory array consisted of a set of pseudo-randomly positioned colored items, and the task was to judge whether the test item was changed compared to the memory item after a retention interval. We found that presenting the items in stereoscopic depth alone hardly affected VWM performance. When combining the two coherent depth cues, a significant larger VWM capacity of the perceptually closer-in-depth items was observed than that of the farther items, but the capacity for the two-depth-planes condition was not significantly different from that for the one-plane condition. Conflicting the two depth cues resulted in cancelling the beneficial effect of presenting items at a closer depth plane. The results indicate that depth perception could affect VWM, and the visual system may have an advantage in maintaining closer-in-depth objects in working memory.